Roh Kudus Meterai Keselamatan Kekal Orang Percaya menurut Efesus 1:13-14 - Yoel Benyamin (Sekolah Tinggi Teologi Kalimantan, 2020)
The many teachings of Christianity that teach about uncertain salvation, including the mistaken opinion of the work of the Holy Spirit as the seal of eternal salvation for believers, create doubts as well as undermine the consistency of the teachings and the authority of the Bible because it seems that its truth becomes relative. This study aims to provide a rebuttal to the opinion that rejects salvation as only God's grace, focus on research on how the work of the Holy Spirit works on salvation in believers. This study uses a qualitative method with a thematic analysis approach and analyzes the text of Ephesians 1: 13-14 as its basis, and considers various views on salvation. This research concludes that the sealing of the Holy Spirit occurs when a person believes in Jesus as Lord and Savior. The Holy Spirit works in the believer, providing protection, assurance, and care for God so that they escape punishment and gain eternal life. The Holy Spirit is a sign that the believer belongs to God because of the redemption of Christ's blood according to the faith response to God's grace.Banyaknya ajaran Kekristenan yang mengajarkan mengenai keselamatan yang tidak pasti, termasuk kekeliruan pandangan mengenai karya Roh Kudus sebagai meterai keselamatan kekal orang-orang percaya, memunculkan kebimbangan sekaligus meruntuhkan konsistensi ajaran dan wibawa Alkitab. Penelitian ini bertujuan memberikan bantahan mengenai pandangan yang menolak keselamatan hanya anugerah Allah, dengan fokus penelitian pada bagaimana karya Roh Kudus mengerjakan keselamatan dalam diri orang-orang percaya. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis tematik dan menganalisis teks Efesus 1:13-14 sebagai dasarnya, serta memperhatikan berbagai pandangan tentang keselamatan. Kesimpulan penelitian ini adalah bahwa pemeteraian Roh Kudus terjadi pada saat seseorang percaya Yesus sebagai Tuhan dan Juru Selamat. Roh Kudus berkarya dalam diri orang percaya, memberi perlindungan, jaminan dan pemeliharaan Allah sehingga luput dari hukuman dan memperoleh kehidupan kekal. Roh Kudus menjadi tanda bahwa orang percaya telah menjadi milik Allah oleh karena penebusan darah Kristus sesuai tanggapan iman kepada kasih karunia Allah.